Experimental Study on the Central Mechanism of Penehyclidine Hydrochloride against Relapse Behavior in Morphine-Dependent Rats - Yufeng Zou; Zhe Jin; Meng Yun Li; Lijuan Tang; Kai Chen (Applied Bionics and Biomechanics)
Objective. This article is mainly to study the central mechanism of penehyclidine hydrochloride against relapse behavior in morphine-dependent rats. Methods. The rats were randomly divided into the blank control group (k), PHC low-dose group (LP according to a body weight of 0.22 mg/kg), middle-dose group (MP according to a body weight of 0.55 mg/kg), high-dose group (HP according to a body weight of 1.38 mg/kg), and administration group, with 40 rats in each group. Each group was randomly divided into 5 subgroups (n=10): 4 h after administration, 7 h after administration, 13 h after administration, 25 h after administration (K48, LP48, MP48, and HP48), and 37 h after administration, and then, Morris water maze experiment and immunohistochemical detection of the rat brain hippocampus were carried out. Results. 4 and 7 hours after administration, compared with group 1, the TchE activity increased and Ach level decreased in groups 2, 3, and 4 and the difference was significant (P<0.05), so the principle of penehyclidine hydrochloride against morphine-dependent rats is that penehyclidine hydrochloride causes cognitive impairment in the brain of mice, thereby achieving antimorphine effects.